HUBUNGAN PERILAKU PENGGUNAAN MASKER DENGAN KEJADIAN MASK INDUCED ACNE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2018 - ANGGRAINI BARUS; ARRIDHA UTAMI PUTRI (LP2MTBM MAKARIOZ, 2022)
Coronavirus Disease 2019 (COVID-19) is a respiratory infection disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), which was first discovered in Wuhan, China on December 31, 2019 and has spread throughout the world. Wearing a mask is the first step in preventing COVID-19. During a pandemic like this, people wear masks more often and for longer than before. It caused an incident of akne lokalisata in the area covered by the mask, which is popularly referred to as